2007
DOI: 10.1073/pnas.0704900104
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity mediated by temporal regulation of the activity of p38 MAPK

Abstract: Circadian clocks are composed of central oscillators, input pathways that transduce external information to the oscillators, and output pathways that allow the oscillators to temporally regulate cellular processes. Little is known about the output pathways. In this study, we show that the Neurospora crassa osmosensing MAPK pathway, essential for osmotic stress responses, is a circadian output pathway that regulates daily rhythms in the expression of downstream genes. Rhythmic activation of the highly conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 61 publications
2
78
0
Order By: Relevance
“…These pathways are likely responsible for controlling both unique and overlapping cellular processes and stress responses that occur at various times in the day, consistent with our finding that not all ccg targets of the MAK-1 pathway behave arrhythmically in ⌬mak-1 cells: circadian rhythms in mRNA accumulation of 2 downstream targets of MAK-1, ccg-7 and NCU08949, were maintained in the ⌬mak-1 strain (data not shown). P-OS-2 peaks in the morning, at a time when the cell is beginning to encounter potential osmotic changes in the environment (22), while P-MAK-1 and P-MAK-2 peak later in the afternoon, at a time when the growth rate of the cells is increasing and conidiation is repressed (57). Interestingly, when MAK-1 was deleted, the levels of ccg-1 mRNA were greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These pathways are likely responsible for controlling both unique and overlapping cellular processes and stress responses that occur at various times in the day, consistent with our finding that not all ccg targets of the MAK-1 pathway behave arrhythmically in ⌬mak-1 cells: circadian rhythms in mRNA accumulation of 2 downstream targets of MAK-1, ccg-7 and NCU08949, were maintained in the ⌬mak-1 strain (data not shown). P-OS-2 peaks in the morning, at a time when the cell is beginning to encounter potential osmotic changes in the environment (22), while P-MAK-1 and P-MAK-2 peak later in the afternoon, at a time when the growth rate of the cells is increasing and conidiation is repressed (57). Interestingly, when MAK-1 was deleted, the levels of ccg-1 mRNA were greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, low-amplitude ccg-1 mRNA rhythms were observed in the deletion strain, albeit with less reproducibility than in wild-type cells. We previously reported that ccg-1 rhythmicity depends upon a functional OS-2 pathway (22), and ccg-1 is induced in response to a variety of stresses (66)(67)(68)(69). Thus, it appears that both MAPK pathways contribute to robust rhythmicity in the expression of some target genes, including ccg-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A twocomponent regulatory system that includes the histidine kinase OS-1 and the response regulator RRG-1 operates upstream of the OS-2 MAPK pathway (24). It has recently been shown that this MAPK cascade is an output pathway for the Neurospora circadian clock (56).…”
mentioning
confidence: 99%
“…The most obvious and prominent circadianly controlled rhythm in N. crassa is that of conidiation, which forms a characteristic conidial banding-pattern on plates or in long glass culture tubes (race tubes). Also, it has been previously reported that RRG-1 of N. crassa functions in an output pathway to regulate circadian rhythmicity, although the upstream HK was not identified (41). Because of the intimate association of the DCC-1 sensor HK with the process of conidiation and the involvement of a two-component system protein (RRG-1) in the regulation of rhythmicity (2), we asked whether DCC-1 also affects this process.…”
mentioning
confidence: 99%